2020
DOI: 10.1016/j.ijscr.2020.06.071
|View full text |Cite
|
Sign up to set email alerts
|

Preprosthesis fracture of femoral and loosening of the femoral prosthesis during closed reduction of hip dislocation: A case report

Abstract: Highlights This is the first reported case of a periprosthetic fracture of femoral and loosening of femoral prosthesis caused by closed reduction. Closed reduction leads to preprosthesis fracture of femoral and loosening of femoral prosthesis is a complex complication that requires operative treatment. Closed reduction should be performed gently to avoid this condition. If this happens, a high-resolution CT examination should be performed immediately to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Simultaneously, excessive valgus could easily lead to dislocation of the prosthesis. Zeng et al [18] reported that closed manual reduction after dislocation would also cause some damage to the prosthesis. Therefore, imaging examination and reduction plan should be fully prepared before reduction.…”
Section: Case Reportmentioning
confidence: 99%
“…Simultaneously, excessive valgus could easily lead to dislocation of the prosthesis. Zeng et al [18] reported that closed manual reduction after dislocation would also cause some damage to the prosthesis. Therefore, imaging examination and reduction plan should be fully prepared before reduction.…”
Section: Case Reportmentioning
confidence: 99%